Netizen Reactions to the Viral Phenomenon of “Tabola Bale”: A Digital Humanities Approach Using Voyant Tools - Aura Prisca Medina; Filosa Gita Sukmono (Universitas Al Azhar Indonesia, 2026)
The development of new media has positioned the audience as active producers of meaning, where the TikTok comment section functions as a primary arena for identity negotiation and participatory culture. This article examines the viral phenomenon of the song